PENGEMBANGAN PERANGKAT LUNAK SISTEM INFORMASI MONITORING MAHASISWA BIDIKMISI BERBASIS WEB MENGGUNAKAN PENDEKATAN DSDM (STUDI KASUS DI UNIVERSITAS SRIWIJAYA) - Dwi Rosa Indah; Mgs Afriyan Firdaus (Jurnal Informatika, 2016)
Development of web-based monitoring and evaluation systems is required to overcome the obstacles and shortcomings in monitoring and evaluation of the academic and non-academic Bidik Misi students so that tasks and responsibilities of university that manages Bidik Misi become more optimal. In this research, the development of system is done using agile method with DSDM model with case study at  Sriwijaya University. Stages of agile method includes planning, risk analysis, engineering and evaluation, while the model DSDM performed on the stages of engineering and evaluation, which includes a DSDM model activity i.e. Backlog, Sprint, DSDM Meeting and Demo. The result is a monitoring system application of academic and non-academic Bidik Misi students which includes features of students management, management of students academic and non-academic as well as monitoring students academic and non-academic to be proposed in a case study Keywords: agile method, DSDM model, monitoring system, system development